Preservação digital: a experiência da pesquisa Guignard - Clarissa Costa e Lima (2007)
Keeping a digital collection for a long period in a usable and interpretable way is called digital preservation. It implicates the maintenance of the integrity, of the technological context, and of the origin description, references and usability of every digital object. Faced to technological obsolescence, the greatest threaten to digital collections, digital preservation is a challenge. The essential aspects considered in a digital preservation policy elaboration are examined in this case study. Besides, it identifies the requirements and needs for information systems designed to this application domain. This work presents the digital preservation applied to the Guignard Research, a study about the life and the work of Alberto da Veiga Guignard, Modernist artist. A great part of the Guignard Researchs collection is held in digital format. Nevertheless, it is impossible to set an ideal, definite and general purpose maintenance plan for any digital collection. However, digital preservation is a risk control policy which aims to a lasting cultural, historical and scientific legacy.